1984
DOI: 10.1071/sr9840149
|View full text |Cite
|
Sign up to set email alerts
|

Moessbauer parameters for ferrihydrites at 4 K

Abstract: The Moessbauer spectra at 4.2K for five ferrihydrites (one natural, four synthetic) have been determined. Two of the samples contained silicon (atomic ratio Si/Fe= 18%, 21%) and one contained aluminium (Al/Fe = 19%). The Moessbauer parameters were calculated from peak positions estimated by a fit of one set of six Lorentzian lines to each spectrum and by judging absorption maxima by eye. Hyperfine magnetic field (H) values were between 50.0 and 50.4 T for pure samples and between 48.3 and 49.2 T for samples co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In spite of the differences in hyperfine field distributions, the M6ssbauer spectra of all these samples are consistent with ferrihydrite being the major Fe-bearing constituent, the magnetic properties of ferrihydrite being known to vary noticeably with crystallinity (Murad & Schwertmann, 1980; and/or chemical composition (Childs et al, 1984). However, because of the indefinite XRD data, the residue of the oxalate treatment must be excluded from this discussion.…”
Section: Mi~ssbauer Spectramentioning
confidence: 74%
“…In spite of the differences in hyperfine field distributions, the M6ssbauer spectra of all these samples are consistent with ferrihydrite being the major Fe-bearing constituent, the magnetic properties of ferrihydrite being known to vary noticeably with crystallinity (Murad & Schwertmann, 1980; and/or chemical composition (Childs et al, 1984). However, because of the indefinite XRD data, the residue of the oxalate treatment must be excluded from this discussion.…”
Section: Mi~ssbauer Spectramentioning
confidence: 74%
“…Murad and Schwertmann (1980) reported that the hyperfine field of lepidocrocite at 4.2 K is 45.8 T, and Vandenberghe et al (1990) reported it to be between 44 and 46 T. Site 4 (11%) could therefore be assigned to lepidocrocite (Table 2). At 4 K, the hyperfine field of ferrihydrite is 48.4 T (Murad and Schwertmann (1980) or between 48.3 and 50.4 T (Childs et al, 1984). In the same study (Childs et al, 1984) the isomer shift varied between 0.48 to 0.57 mm/s.…”
Section: Mössbauer Spectroscopymentioning
confidence: 91%
“…At 4 K, the hyperfine field of ferrihydrite is 48.4 T (Murad and Schwertmann (1980) or between 48.3 and 50.4 T (Childs et al, 1984). In the same study (Childs et al, 1984) the isomer shift varied between 0.48 to 0.57 mm/s. Comparison of these values with the site 3 values shown in Table 2, indicates that site 3 (18%) could be assigned to ferrihydrite.…”
Section: Mössbauer Spectroscopymentioning
confidence: 91%
“…The present <T B > values between 40 and 12 °K therefore imply a mean particle size in the range of 3-4 nm. The inclusion of Si in the lattice, which is likely to occur on precipitation of iron oxyhydroxides in seawater, will reduce the value of <T B > (Childs et al, 1984;Chadwick et al, 1986). The mean particle size is therefore probably somewhat larger than 3-4 nm, but this cannot be accurately quantified.…”
Section: Dsmentioning
confidence: 97%